Effect of Orientation on Thermal Performance of Fully Enclosed Courtyard in Tropical Climate - Modi Sule Zango; IIiyasu Sanke Isyaku; Timothy Marcus Kogi; Amos Danladi; Bilkisu Priscilla Sambo; Emmanuel Adamu Gado (Scholars Digest Publishing, 2022)
Globalization has resulted in pollution, carbon emissions, climate change, and an insufficient supply of natural resources. As a result, research is required to increase the thermal performance of buildings. In this regard, using a courtyard as a building component is one of the most sustainable ways to improve the building's thermal performance and microclimate. While utilizing the Envi-met program on the configurations chosen for the fully enclosed courtyard, this study investigated the effect of orientation on the fully enclosed courtyard's thermal performance. 1:1:1 and 1:2:1 are examples of this setup. The orientations considered in this example were N-S, E-W, NE-SW, and NW-SE. The air temperature, mean radiant temperature and physiological equivalent temperature were measured during simulations of two configurations of the fully enclosed courtyard. According to the research, the air temperature, mean radiant temperature and physiological equivalent temperature rise as the size of the courtyard grows. As a result, the air temperature in the 1:1:1 courtyard arrangement is lower than in the 1:2:1 courtyard design.
Keywords: Courtyard, Simulation, Orientation, Air temperature and Mean Radiant Temperature.